Epidemiological and Genetic Aspects of NAFLD and NASH in Mexico. Issue 2 (10th March 2022) - Vidal‐Cevallos, Paulina; Torre, Aldo; Mendez‐Sanchez, Nahum; Uribe, Misael; Chavez‐Tapia, Norberto C.
Abstract :